Immediate plastic surgery closure at index spinal surgery minimizes complications compared to delayed reconstruction: A retrospective cohort review. Issue 8 (August 2020) - Sawh-Martinez, Rajendra; Lin, Alex; Timberlake, Andrew; Wu, Robin T.; Shah, Ajul; Chen, William; Steinbacher, Derek; Diluna, Michael; Au, Alexander
Summary: Background: Complex spine surgery in patients with major comorbidities leads to increased need for midline back wound reconstruction by plastic surgeons. Literature suggests that back wound reconstruction concurrent with high-risk immediate/index spine surgery may lead to fewer complication. This study aimed to validate this claim in a large cohort treated at a tertiary center. We hypothesize that immediate reconstruction may lead to fewer adverse events in comparison to delayed reconstruction. Methods: This was a retrospective single-center review of 659 patients who underwent spinal surgery with/without reconstruction by plastic surgeons between November 2011 and December 2015. Three main cohorts were evaluated: patients who underwent spinal surgery with no reconstruction, patients with delayed reconstruction after spine surgery, and patients with immediate back wound reconstruction with index spine surgery. Demographic, clinical, and outcomes data were collected from electronic medical records. Primary endpoints were the incidence of any complications such as dehiscence, infection, seroma/hematoma, and exposed hardware. The secondary endpoint was return to the operating room and most recent follow-up. Results: Forty-three patients underwent index reconstruction (follow-up 25.3 ± 12.7 months), 33 were delayed (follow-up 23.7 ± 12.5 months), and 583 had no reconstruction (follow-up 22.1 ± 15.2 months). Patients who underwent index reconstruction had more spinal levels involved than delayed reconstruction (7.8 ± 0.75  vs 5.6 ± 0.68 ; p  = 0.03). The overall complications rate was 7.7%, most commonly wound dehiscence (2.7%), infections (0.9%), exposed hardware (2.0%), cerebrospinal fluid leaks (0.6%), and return to OR (3.8%). Patients who underwent index spinal wound reconstruction had a significantly lower complication rate (4.65%) than secondary spinal surgery patients (27.3%; p  = 0.048). Conclusions: The data confirmed significantly decreased complication rates for index back wound reconstructions for high-risk patients compared to delayed spine wound reconstruction. Increased rates of wound dehiscence, exposed hardware, and revisions occurred with delayed reconstruction. Early employment of tension free, robust vascular flap closure may attribute to a decreased complication profile.